The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1259/dmfr/49065239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternative photostimulable phosphor plates erasing times on subjective digital image quality

Abstract: Objective: To evaluate the influence of alternative erasing times of DenOptixH (Dentsply/ Gendex, Chicargo, IL) digital plates on subjective image quality and the probability of double exposure image not occurring. Methods: Human teeth were X-rayed with phosphor plates using ten different erasing times. Two observers evaluated the images for subjective image quality (sharpness, brightness, contrast, enamel definition, dentin definition and dentin-enamel junction definition) and for the presence or absence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
4
0
4
Order By: Relevance
“…12,18,19 After evaluating the effect of different erasing times on proximal caries diagnosis, Melo et al 12 reported no significant difference in both pixel intensity values and diagnostic accuracy of observers. Since the effect of various erasing times was tested, the methods of the former and the presented study were basically not the same; therefore, the comparison of the results may not be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…12,18,19 After evaluating the effect of different erasing times on proximal caries diagnosis, Melo et al 12 reported no significant difference in both pixel intensity values and diagnostic accuracy of observers. Since the effect of various erasing times was tested, the methods of the former and the presented study were basically not the same; therefore, the comparison of the results may not be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies [16,21,23] evaluated the effect of different times of erasing data from PSPs on the quality of inter-proximal caries detection; Melo reported no effect on caries detection ability [16]. Result comparison between Melo's study and our study regarding this matter is not feasible due to fundamental and structural differences.…”
Section: Fig 1 Sample Teeth In Contact Mounted In a Silicone Block mentioning
confidence: 56%
“…26 Silme süresinin değerlendirildiği farklı çalıĢmalar olmakla birlikte Melo ve ark. 29 plakların en az 25 saniye süreyle 1700 lux ıĢığa maruz bırakılması gerektiğini bildirmiĢlerdir. Bu sürenin altındaki uygulamalarda görüntünün kontrast, parlaklık, keskinliğinin azaldığı, mine, dentin ve mine-dentin sınırının net izlenemediği ve görüntüde "çift görüntü" oluĢtuğu rapor edilmiĢtir.…”
Section: Tarama ġģLemiunclassified
“…Bu sürenin altındaki uygulamalarda görüntünün kontrast, parlaklık, keskinliğinin azaldığı, mine, dentin ve mine-dentin sınırının net izlenemediği ve görüntüde "çift görüntü" oluĢtuğu rapor edilmiĢtir. 29 Tarayıcıya bağlı olarak, görüntüde fazladan horizontal beyaz çizgi oluĢması, tarama parametrelerinin optimal olmasına karĢılık görüntünün çok parlak olması (ġekil 3), ekranda görüntünün sadece bir kısmının oluĢması, görüntü boyutunun küçülmesi, farklı iki görüntünün süperpoze olması (ġekil 4) gibi artefaktlar oluĢabilir. Bu gibi durumlarda plaklar taranırken silinmemiĢse aynı plak yeniden tarandığında görüntünün düzgün bir Ģekilde elde edildiği bildirilmiĢtir.…”
Section: Tarama ġģLemiunclassified